Proceedings of the 49th Annual ACM SIGACT Symposium on Theory of Computing 2017
DOI: 10.1145/3055399.3055417
|View full text |Cite
|
Sign up to set email alerts
|

Strongly refuting random CSPs below the spectral threshold

Abstract: Random constraint satisfaction problems (CSPs) are known to exhibit threshold phenomena: given a uniformly random instance of a CSP with n variables and m clauses, there is a value of m = Ω(n) beyond which the CSP will be unsatisfiable with high probability. Strong refutation is the problem of certifying that no variable assignment satisfies more than a constant fraction of clauses; this is the natural algorithmic problem in the unsatisfiable regime (when m/n = ω(1)).Intuitively, strong refutation should becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 25 publications
4
75
0
Order By: Relevance
“…Initiated by the work of [BBH + 12], who showed that polynomial time algorithms in the hierarchy solve all known integrality gap instances for Unique Games and related problems, a steady stream of works have developed efficient algorithms for both worst-case [BKS14, BKS15, BKS17, BGG + 16] and average-case problems [HSS15,GM15,BM16,RRS16,BGL16,MSS16a,PS17]. The insights from these works extend beyond individual algorithms to characterizations of broad classes of algorithmic techniques.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Initiated by the work of [BBH + 12], who showed that polynomial time algorithms in the hierarchy solve all known integrality gap instances for Unique Games and related problems, a steady stream of works have developed efficient algorithms for both worst-case [BKS14, BKS15, BKS17, BGG + 16] and average-case problems [HSS15,GM15,BM16,RRS16,BGL16,MSS16a,PS17]. The insights from these works extend beyond individual algorithms to characterizations of broad classes of algorithmic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Key examples are finding solutions of random constraint satisfaction problems (CSPs) with planted assignments [RRS16] and finding planted optima of random polynomials over the n-dimensional unit sphere [RRS16,BGL16]. The latter formulation captures a wide range of unsupervised learning problems, and has led to many unsupervised learning algorithms with the best-known polynomial time guarantees [BKS15, BKS14, MSS16b, HSS15, PS17, BGG + 16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This leaves open a wide range of densities from constant to n k−2 2 where no polynomial time algorithms for refutation are known. It was recently shown that degreeÕ(n ε ) sum-of-squares semidefinite programs can refute random k-SAT instances at density n ( k−2 2 )(1−ε) for all ε ∈ (0, 1), thereby yielding a subexponential time refutation algorithm for all densities in this range [RRS16]. However, the problem By using the fact that the k-XOR predicate and the k-SAT predicate support (k −1)-wise uniform distribution on satisfying assignments, the following corollary is immediate.…”
Section: Introductionmentioning
confidence: 99%